Porous ground treatments for propeller noise reduction in ground effect - Hasan Kamliya Jawahar; Liam Hanson; Md. Zishan Akhter; Mahdi Azarpeyvand (Scientific Reports)
Abstract This study investigates the aerodynamic and aeroacoustic behavior of propellers operating in ground-effect conditions, with an emphasis on the impact of porous ground surface treatments. The investigation explores the potential of porous materials to reduce propeller noise near the ground, a major barrier to the acceptance and integration of Urban Air Mobility (UAM) systems. Experiments were conducted in an anechoic chamber using an APC $$10 × 5.5$$ inch propeller in a pusher configuration. The setup used a rigid flat plate to act as the ground plane at various distances from the propeller. The ground plane was treated with three types of porous foams, each with different pore densities and thicknesses. Noise measurements were taken using a polar array of microphones positioned in both near-field and far-field locations. The results show that porous surface treatments significantly enhance noise suppression. Coherence analysis revealed that porous treatments improve the spatial consistency of acoustic signals, making noise propagation more predictable and controllable. The study also highlights that the interaction between wake flow and porous surfaces leads to greater noise suppression and stability in the hydrodynamic pressure field. These findings have significant implications for designing quieter, more efficient UAM vehicles, aiding their integration into urban environments.